BIOFIKSASI CO2 OLEH MIKROALGA Spirulina sp DALAM UPAYA PEMURNIAN BIOGAS - Fegi Yuliandri; Yudha Duta Utama; Luqman Buchori (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
The main component of biogas CH4,it is a renewable energy product that is expected to be the fuel gas. However, the presence of CO2 in the biogas decrease it’s heating value. The Purification of biogas is a solution to increase the heating value. One of eco-friendly way to purify biogas eco-friendly is by using microalgae Spirulina sp which has the CO2 Biofixation ability. This research intends to Determine the most effective flow rate of tubular type photobioreactor by using microalgae spirulina in absorbing CO2 and determine the optimum concentration of CO2 that can be absorbed by the microalgae Spirulina sp. This research is using flow rate of gas mixture (30% CO2 gas composition V: air 70% V) 0.2 L / sec, 0.5 L / sec, 1 L / sec, and 1.5 L / sec. And using composition of the feed gas (flow rate of 0.5 L / min) was 25% V CO2, 75% air V; CO2 30% V; air 70% V; V 35% CO2, 65% air V; CO2 40 % V, 60% air. The results obtained that the optimum flow rate for CO2 absroption is the flowrate  0.5 L / min with a feed gas composition CO2: air (30:70). Highest CO2 absorption amounted to 0.47%, and it doesnt reach the desired target of purification. So it needs to re-design the research’s tools to increase the amount of CO2 absorbed.